EAI4CC: deciphering lung and colon cancer categorization within a federated learning framework harnessing the power of explainable artificial intelligence - Mim, Ankhi Akter; Ashakin, Kazi Habibul; Hossain, Sadat; Orchi, Nabiha Tasnim; Him, Al Shahriar (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.